Phytochemical Studies and Antimicrobial Screening of Non/Less-Polar Fraction of Psoralea corylifolia by Using GC-MS - Syed Tariq Ali; Hina Anwar; Syed Kashif Ali; Sobiya Perwaiz; Talat Yasmeen Mujahid; Abdul Wahab; Syed Abdus Subhan (Journal of Basic & Applied Sciences, 2015)
Psoralea corylifolia is a well-known medicinal plant, traditionally used against several diseased conditions. The present study was conducted to investigate the phytochemical composition and antimicrobial activity of P. corylifolia seeds. Non/less-polar fraction of methanolic seed extract was subjected to gas chromatography-mass spectrometry (GC-MS) for phytochemical analysis. A total of fourteen compounds were identified which include aromatic, sesquiterpenes, furocoumarins, sterols, fatty acid and their methyl esters. The predominant compounds were epoxycaryophyllene (3), isopsoralen (6), psoralen (7) and bakuchiol (9). Identification of these compounds was also strongly supported by Kovat’s Retention Indices. Furthermore, the n-hexane soluble fraction showed significant antimicrobial activity against several bacterial strains. P. corylifolia seeds represented a unique chemical composition with considerable antimicrobial activity which not only validates their traditional medicinal uses but also indicates their potential as a source of natural antimicrobial compounds.